STUDI PERBANDINGAN KUALITAS ORGANOLEPTIK TELUR PUYUH DIREBUS DENGAN LARUTAN GARAM 5%) - Khoiri, Alifatul (PPPM POLTESA, 2023)
Salted quail eggs are a type of processed egg product that have a distinctive salty flavor. This flavor depends on the concentration of the salt solution used during the boiling process. The aim of this study was to compare the organoleptic characteristics of salted quail eggs boiled in a 5% (w/v) salt solution with those boiled in clean water. The salted quail eggs were prepared by coating the eggs with a mixture of salt and ash, and then boiling them in either the salt solution or the clean water. The study results indicated that there was no significant difference (P>0.05) between the two samples in terms of taste, firmness, texture, and aroma. However, most panelists favored the salted quail eggs boiled in the salt solution because they had a slightly stronger fishy aroma and a slightly higher salinity.